ANALYSIS OF THE COURSE OF PREGNANCY AND BIRTH, PERINATAL OUTCOMES IN LARGE FETUS - Tursunoi Ismoiljonovna Murodova (Galaxy International Interdisciplinary Research Journal, 2022)
The article provides for the problem of childbirth with a large fetus in recent years has become increasingly relevant, which is explained not only by the increase in the frequency of macros, but also by the high level of complications of pregnancy and childbirth, perinatal morbidity, maternal injury.